Women involvement in the informal caregiving field: A perspective review - Rexhaj, Shyhrete; Nguyen, Alexandra; Favrod, Jérôme; Coloni-Terrapon, Claire; Buisson, Leslie; Drainville, Anne-Laure; Martinez, Debora (Frontiers in Psychiatry, 2023)
The patient recovery process of individual with mental health disorder is reinforced if they are connected with their community and supported by relatives. The literature has shown that caregivers are important, although their roles can lead to alterations in their own health; and women are the most involved in this role. The present review investigated women’s involvement in the informal caregiver scientific field. A literature review indicated gender differences; researchers who are women are more interested in this field than men. Even with a good representation of women in this scientific field, the results showed a statistically significant gender difference for the first and second authors, whereas there was no significant gender difference among the last authors. More efforts must be made to recognize the importance of women’s involvement in research because they raise a specific important field important. Family caregivers are key players in the healthcare system, but to date, there has been little recognition of their enormous contribution. Our results also indicated the informal caregiver role is filled more by women than by men, which creates social inequalities in many domains, especially in opportunities at the professional level. Tailored interventions are required to address the specific needs and issues of family caregivers. A better redistribution of unpaid work, such as informal caregiving, compared to paid work must be made to respect gender in social existence.